P-275 Delayed blastocyst development is associated with a higher level of progesterone: the missing link in the chain. (30th June 2022) - Villanacci, R; Buzzaccarini, G; Pagliardini, L; Marzanati, D; Alteri, A; Vanni, V.S; Candiani, M; Papaleo, E
Abstract: Study question: Is there an association between progesterone (P) level on the day of trigger and blastulation rate on day 5 versus day 6? Summary answer: Higher level of progesterone on the day of trigger is associated with lower blastulation rate on day 5 versus day 6. What is known already: Premature progesterone elevation is known to determine a premature advanced endometrium by worsening endometrial-embryo asynchrony and affecting live birth rate during fresh cycles. To overcome the detrimental effect on the implantation window shift, freeze-all-strategy was introduced. Questions have been raised about the possible impact of progesterone also on oocyte's quality and embryo's euploidy rate. Studies on preimplantation genetic testing (PGT) cycles have demonstrated no differences in terms of fertilization, blastulation, euploidy and pregnancy rates. However, no studies have evaluated whether progesterone may impact blastocyst development in terms of blastulation rate. Study design, size, duration: This was a retrospective cohort study with autologous IVF cycles performed at our institution from January 2019 to December 2021. 2819 IVF cycles were screened for inclusion. A total of 888 IVF cycles were included. The primary outcome was to compare blastulation rate on day5 versus day6 in terms of percentage of formed blastocysts on day5 versus day6 according to progesterone level at trigger. Participants/materials, setting, methods: Patients between 18 and 42 years of age who underwent blastocyst culture of the whole cohort of embryos formed were included. Blastocyst evaluation was performed by a team of expert embryologists according to the Istanbul Consensus. We performed the Kruskal-Wallis test to assess differences between groups (blastulation rate according to progesterone level at trigger) and a multiple logistic regression analysis to evaluate association between the presence/absence of full blastocyst on day5 and progesterone levels. Main results and the role of chance: A total of 3249 blastocysts were analyzed. The blastulation rate per total number of cycles was 39.4% for day-5 blastocyst, 54.0% for day-6 blastocyst, and 6.6% for day-7 blastocyst. After dividing progesterone level in quartiles (Q1, P < 0.51 ng/ml; Q2, 0.51 ng/ml ≤ P < 0.82 ng/ml; Q3, 0.82 ng/ml ≤ P < 1.21 ng/ml; Q4, P ≥ 1.21 ng/ml), we observed a progressive delay in blastocyst development according to the increasing level of progesterone at trigger (with a median blastulation rate on day5 of 50.00% for Q1 versus 40.00% for Q2, 30.00% for Q3 and 30.00% for Q4, p < 0.001). After adjusting for confounding factors, the the probability to observe at least one full blastocysts on day5 was significantly reduced for Q3 (OR = 0.44, CI 0.28-0.70, p < 0.001) and Q4 (OR = 0.31, CI 0.19-0.48, p < 0.001) compared to Q1 (reference). Limitations, reasons for caution: The retrospective nature of the study and potential variability between our study center's laboratory protocol(s) and blastocyst culture medium used compared to those of other reproductive centers may limit the external validity of our findings. A well-designed multicenter study is needed to further extend and validate our results. Wider implications of the findings: This study suggests that progesterone level on the day of induction may affect blastocyst development. Thus, embryologists should not be worried by a slow growing embryo and should expect different blastulation rate on day 5/6 according to progesterone level. Trial registration number: Not applicable